2003
DOI: 10.1093/hmg/ddg204
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of the silenced and imprinted alleles of ARHI is associated with increased histone H3 acetylation and decreased histone H3 lysine 9 methylation

Abstract: ARHI has been identified as a maternally imprinted tumor suppressor gene that maps to chromosome 1p31 and whose expression is markedly down-regulated in breast cancer. To explore possible mechanisms that could silence ARHI expression, we have tested the importance of DNA methylation, histone acetylation and histone methylation in regulating ARHI expression. We found that treatment with CpG demethylating agents and/or histone deacetylase inhibitors could reactivate both the silenced and the imprinted alleles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 37 publications
3
59
0
Order By: Relevance
“…Epigenetic modifications of DNA and histones are involved in gene regulation by altering chromatin structure (Fujii et al, 2003). In this report we demonstrated that DNA methylation and histone modifications regulate HSulf-1 expression and Epigenetic silencing of HSulf-1 J Staub et al provided the first evidence of methylation in combination with chromatin histone modification as a mechanism of HSulf-1 inactivation in ovarian cancer.…”
Section: Discussionmentioning
confidence: 52%
“…Epigenetic modifications of DNA and histones are involved in gene regulation by altering chromatin structure (Fujii et al, 2003). In this report we demonstrated that DNA methylation and histone modifications regulate HSulf-1 expression and Epigenetic silencing of HSulf-1 J Staub et al provided the first evidence of methylation in combination with chromatin histone modification as a mechanism of HSulf-1 inactivation in ovarian cancer.…”
Section: Discussionmentioning
confidence: 52%
“…Normal breast epithelial cells NBE234 and NBE231 and normal ovarian epithelial cells OSE113, OSE115, OSE106, and OSE120 were cultured as described previously (29). SKBr3, BT20, MDA-MB-468, and MDA-MB-435 breast cancer cells were maintained in RPMI 1640 supplemented with 10% fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…The ChIP assay was carried out as previously described (Fujii et al, 2003). The PCR conditions for the EZH2 gene (Gene Accession Number NC_000007.12) promoter, which contains or does not contain Elk-1 biding motifs, were applied with the following three primer pairs: ChIP primer 1 which contains three Elk-1 binding motifs (5 0 to 3 0 ): TTAAAACCGTTACCA CCCCCGAGTTTTGAA and TTCGCTGTAAGGGACGCC ACTGGCCGTGT, ChIP primer 2 which contains two Elk-1 binding motifs (5 0 to 3 0 ): AACTCTGCGGCGCCGGTT CCCGCCAAGA and TTCGCTGTAAGGGACGCCACTG GCCGTGT and ChIP primer 3 which does not contain any Elk-1 binding motifs (5 0 to 3 0 ): ACGAACAGTGGA AGGGTCTG and GGAGTTTCGCTCTGGTTGTC.…”
Section: Chromatin Immunoprecipitation Assaymentioning
confidence: 99%